Global Principles for Professional Learning in Gifted Education and Italian Primary Teachers - Brazzolotto, Martina; Phelps, Connie (International Journal for Talent Development and Creativity, 2021)
Aligned with the 10 Global Principles for Professional Learning in Gifted Education (WCGTC, 2021), this exploratory study investigated the co-construction of inclusive differentiated instruction for a fourth grade gifted student with three general education teachers in a North Italy public education primary school using learning menus and learning contract strategies. The research questions examined responses of general education teachers toward (a) an identified gifted student, (b) inclusion practices in the primary classroom, and (c) co-constructed interdisciplinary curricula for a gifted student. Conducted during a six-week timeframe, the primary researcher conducted Pre- and Post-Intervention Focus Groups, established an instructional baseline, planned interdisciplinary activities in five academic subjects, suggested lesson extensions, and concluded with a Parent Interview. The primary researcher provided professional learning experiences in accordance with the Italian Ministry of Education ministerial law n. 562 (2019) that mandated inclusion of children with giftedness in the category of special education needs. Analysis of Pre- and Post-Intervention Focus Groups results indicated improved dispositions of teachers toward a gifted student in general education primary classrooms, development of inclusive classroom practices with guidance from a gifted education specialist, and documented competencies co-constructing interdisciplinary curricula integrated with 10 Global Principles for Professional Learning in Gifted Education.